2019
DOI: 10.1136/bmjopen-2018-023630
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-sweetened beverage (SSB) consumption, correlates and interventions among Australian Aboriginal and Torres Strait Islander communities: a scoping review

Abstract: ObjectivesSugar-sweetened beverage (SSB) consumption in Australian Aboriginal and Torres Strait Islander people is reported to be disproportionally high compared with the general Australian population. This review aimed to scope the literature documenting SSB consumption and interventions to reduce SSB consumption among Australian Aboriginal and Torres Strait Islander people. Findings will inform strategies to address SSB consumption in Aboriginal and Torres Strait Islander communities.MethodsPubMed, SCOPUS, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 58 publications
0
20
1
Order By: Relevance
“…While the present study indicates that SSB consumption is common among young Aboriginal and Torres Strait Islander children, this is not an issue specific to this population (18) ; there is clear evidence of a high prevalence of SSB intake among infants in the total Australian population (1,17,19,86) and in other countries including Finland (87) and Brazil (88) . Efforts to reduce SSB consumption by Aboriginal and Torres Strait Islander children could be broadened to lead to health benefits at the population level.…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…While the present study indicates that SSB consumption is common among young Aboriginal and Torres Strait Islander children, this is not an issue specific to this population (18) ; there is clear evidence of a high prevalence of SSB intake among infants in the total Australian population (1,17,19,86) and in other countries including Finland (87) and Brazil (88) . Efforts to reduce SSB consumption by Aboriginal and Torres Strait Islander children could be broadened to lead to health benefits at the population level.…”
Section: Resultscontrasting
confidence: 61%
“…There is a high prevalence of SSB consumption in Australia, and particularly high consumption prevalence and volume among Aboriginal and Torres Strait Islander peoples (18)(19)(20) . While the measurement approaches and populations have varied across studies, there is consistent localised and national quantitative evidence of high SSB intake by Aboriginal and Torres Strait Islander children in the first 3 years of life (Table 1) (18,(21)(22)(23)(24)(25)(26) . For example, data from the National Aboriginal and Torres Strait Islander Nutrition and Physical Activity Survey (NATSINPAS) indicated that 26•0 (95 % CI 13 •5, 38•5) % of Aboriginal and Torres Strait Islander children aged 2-3 years had consumed cordial on the day prior to interview, compared with 10•3 (95 % CI 6•4, 14•2) % of non-Indigenous children in the Australian Health Survey (18,21,22) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important subpopulation due to health disparity observed between Aboriginal and Torres Strait Islander and non‐Aboriginal Australians. Review of existing literature and data gathered as part of the National Aboriginal and Torres Strait Islander Nutrition and Physical Activity Survey (NATSINPAS) have found the prevalence of SSB consumption is disproportionately high among Aboriginal people 45,46 …”
Section: Implications For Public Healthmentioning
confidence: 99%
“…Sugar‐sweetened beverage (SSBs) are one of the largest sources of free sugars in the diet, with excess consumption linked with NCDs. Health impacts are greatest in disadvantaged groups. NCDs pose substantial health and economic burdens.…”
Section: Introduction To Sugar‐sweetened Beverage Taxesmentioning
confidence: 99%